Alimentary canal of the blow fly Chrysomya megacephala (F.) (Diptera: Calliphoridae): An emphasis on dissection and morphometry - Boonsriwong W. (2014)
The alimentary canal is a major organ system that is often involved in the transmission of pathogens to humans from insects that serve as vectors of disease. In this study, we investigated the alimentary canal of the blow fly, Chrysomya megacephala (F.) (Diptera: Calliphoridae), highlighting the description for dissection and morphometric analysis of each organ. Dissection was performed in a phosphate buffer solution (pH=7.4) on 3rd instar larvae (three to four days old) and on both male and female adults (seven days old). Larval dissection was accomplished using two fine forceps to open the specimens from the posterior end and proceed anteriorly toward the cephalic segment. Meticulous dissection of the anterior end was vital for observation of the delicate salivary ducts, crop duct, and esophagus. Overall length of the 3rd instar alimentary canal measured 89.15 mm (range 81.40-99.70 mm). The midgut comprised the longest portion, measuring 46.35 mm (range 40.00-52.00 mm; n = 30) of the entire canal. Adult dissection was also performed from abdomen to head. Morphometric analyses revealed that the alimentary canal of males and females were relatively similar. No statistical differences were found between the entire length of the alimentary canal from mouth to anus (excluding all branches of the salivary glands, crop, and Malpighian tubules) of males and females. The alimentary canals of males measured 36.23 mm (range 32.60-41.20 mm) in length; whereas, those of females measured 37.23 mm (range 32.70-42.15 mm). Two-thirds of the entire canal length was comprised of midgut in each sex. © 2011 The Society for Vector Ecology.